Digital lensless holographic microscopy and applications (2017)
(Eng) The principles and some applications of the digital lensless holographic microscopy (DLHM) to study the microworld are shown in this paper. The recording and reconstruction processes of the DLHM are analyzed to study its lateral resolution power. The effect of the spatial coherence in the study of a section of the head of a Drosophila melanogaster fly are presented. DLHM is applied to study dwynamic and static colloidal systems as a proof of the capability of achieving micrometer spatial lateral resolution without the use of lenses.